GE_GERICHTE P/9226/2014 vom 13. Januar 2015 - GE Cour de justice (2015)
ORDONNANCE PÉNALE; PEINE D'ENSEMBLE; VOIE DE DROIT; COMPÉTENCE RATIONE MATERIAE; LACUNE(LÉGISLATION) | CPP.393; CP.49; CPP.356; CPP.34; LaCP.3.ze; CPP.91.4; CPP.135